Introduction - Laura Gaffuri (Reti Medievali Rivista, 2010)
Is there a Franciscan political thought? And a Franciscan policy and practice? Published in 2005, the book of Paolo Evangelisti studied the relationship between the political work of some Franciscan friars in the Catalan-Aragonese realm between the fourteenth and fifteenth century and their theological culture. Such relations open new research areas for scholars of political thought among Middle Ages and early modern.